Update on the developmental consequences of cannabis use during pregnancy and lactation. Issue 15 (7th August 2020) - Grant, Kimberly S.; Conover, Elizabeth; Chambers, Christina D.
Abstract: There is a strong increase in prevalence trends for cannabis use during pregnancy and lactation as more states legalize use of this drug. Information on the teratogenic risk of cannabis is limited but some important themes can be gleaned. Studies have not found a unique phenotypic signature of prenatal exposure but an increased risk of congenital anomalies, particularly gastroschisis, has been reported. Changes in fetal growth have been described in some epidemiological studies but long‐term patterns of physical growth appear unaffected. Prenatal exposure to cannabis is not generally associated with reductions in global IQ but specific cognitive skills, especially attention and memory, can be negatively impacted. Long‐term impacts on psychological health include increased rates of depressive symptoms and anxiety as well as delinquency. Relatively little is known about the risk of maternal cannabis use during lactation but data suggest that infant exposure is relatively low compared to maternal exposure. As delta‐9‐tetrahydrocannabinol (THC) levels increase to meet consumer demand and routes of exposure diversify, there is a strong need for prospective birth‐cohort studies that collect biological samples to quantify exposure. Data from such studies will be critical to overcoming the weaknesses of past cannabis research and are essential to establishing reliable information on the risks of maternal use. Until that time, health care providers should be encouraged to talk about the risks and benefits associated with cannabis use during pregnancy and lactation with their patients, emphasizing that fetal and neonatal risks cannot be excluded at this time.